Deep phlegmons of the sole of the foot in the diabetic - Trostchansky, José; Salgado, Moisés; Balboa, Oscar (Cirugía del Uruguay, 2021)
Five cases of deep abcesses in the sole foot of diabetic patients are presented. An analysis is made of their anatomo-clinical and pathological characteristics. Early surgical treatment consists of full drainage of the suppurative focus.